Tiempo de uso de los dispositivos móviles y su relación con la ansiedad en los estudiantes de décimo y undécimo grado en una institución educativa privada de la ciudad de Santa Marta (2023)
This project aims to determine the relationship between the use of mobile devices and screen dependency, which can affect anxiety levels in tenth and eleventh grade students from a private educational institution in the city of Santa Marta, Colombia. The research is framed within the positivist paradigm and adopts a quantitative approach, with a population sample of thirty students between the ages of fourteen and seventeen. Two instruments were used for data collection: the first one is a CMARS questionnaire, which includes questions aimed at identifying the anxiety levels of the surveyed students. In the analysis of results, a correlation between students who had greater exposure in terms of screen time and usage and the appearance of anxiety symptoms is not evident